Determinants of Outpatient Patient Loyalty Based on the Loyalty Triangle at Samarinda Medika Citra Hospital in 2025 - Bambang, Ayu Wulansari; Baso, Bachtiar; Satrianegara, Faiz; Hasnany, Hasnany; Latu, Saparuddin; Mahmudah, Rifa’atul; Patarai, Muhammad Idris (INHEALTH : INDONESIAN HEALTH JOURNAL, 2025)
The Loyalty Triangle is a crucial framework influencing patient loyalty in hospitals, comprising business process variables, perceived value, and database management. This study aims to analyze the determinants of outpatient patient loyalty at Samarinda Medika Citra Hospital. Conducted with a quantitative research design and a cross-sectional approach, the research involved 150 respondents selected through purposive sampling. Data analysis utilized the Spearman Rank test to explore relationships between variables, while ANOVA and logistic regression tests assessed the impact of independent variables on patient loyalty. The Spearman test results indicated strong correlations: business processes (p = 0.718), perceived value (p = 0.842), and database management (p = 0.751) were all significantly related to patient loyalty. Multiple linear regression analysis further revealed that business processes (p = 0.086), perceived value (p = 0.081), and database management (p = 0.071) each significantly affect loyalty. The ANOVA test yielded an F-value of 106.510 with a significance level of 0.001, confirming the model's effectiveness. The study concludes that enhancing business processes, perceived value, and database management can significantly improve patient loyalty. It is recommended that the hospital invest in staff training to improve interpersonal communication and service quality for patients and their families.